Consumer Behavior and the Adoption of Electric Vehicle in Indonesia - Sunaini Rofi'ah; Egi Pranajaya (Universitas Islam Negeri (UIN) Salatiga, 2025)
This study explores the key factors influencing the adoption of electric vehicles (EVs) in Indonesia, focusing on economic conditions, government policies, infrastructure availability, and public awareness. Using a qualitative approach, relevant peer-reviewed sources were carefully selected and thematically analyzed. The findings reveal that government subsidies and supportive policies have significantly increased EV adoption, particularly between 2020 and 2022. Improved charging infrastructure in urban areas has alleviated range anxiety, while macroeconomic conditions influence consumer purchasing power. However, significant challenges remain, including limited rural infrastructure, high upfront costs, and low public awareness. The study makes a theoretical contribution by integrating consumer behavior theories with economic and policy factors, offering a comprehensive framework that enhances the understanding of EV adoption in developing countries and serves as a foundation for future research and policymaking.